Dialogues between Psychology and Art: an Overview of Those Researches Made in Costa Rica (1986-2019) - Soto Rodríguez, Mario Andrés (2021)
This article presents a balance of the investigations that have established a dialogue between psychology and art, in Costa Rica, during the period 1986-2019. The quantitative and descriptive methodological approach consists of the search, review and systematization of academic works that follow the aforementioned dialogue, for the subsequent construction of a database from which the data presented here is derived. Among the main results, it is found that most of the works that make this link between fields are presented as undergraduate thesis (in psychology), produced mainly by women; a substantial increase in this type of studies has been detected in recent years, with the UCR being the main institution that houses them. Literature is the art form most questioned by psychology, using mostly psychoanalytic approaches to do so, through at least three main methodologies: Psychoanalytic Readings, Deep Hermeneutics and Content Analysis.